Tourism demand modelling : an empirical study on the tourism industry in Singapore. - Lin, Lynette Taixun. (2008)
The contribution of the tourism industry is of great importance to the Singapore economy. The purpose of this research is to investigate the demand for tourist travel from Australia, China, Japan and Malaysia. Quarterly data from the period 1995 to 2000 are used. Themacroeconomic variables chosen to explain tourism demand are per capita income, relative prices, and exchange rate, in conjunction with dummy variables.